Microenvironments in tuberculous granulomas are delineated by distinct populations of macrophage subsets and expression of nitric oxide synthase and arginase isoforms - Mattila, Joshua T. (2013)
Macrophages in granulomas are both anti-mycobacterial effector and host cell for Mycobacterium tuberculosis(M.tb), yet basic aspects of macrophage diversity and function within the complex structures of granulomas remain poorly understood. To address this, we examined myeloid cell phenotypes and expression of enzymes correlated with host defense in macaque and human granulomas. Macaque granulomas had upregulated inducible and endothelial nitric oxide synthase (iNOS and eNOS) and arginase (Arg1 and Arg2) expression and enzyme activity compared to non-granulomatous tissue. Immunohistochemical analysis indicated macrophages adjacent to uninvolved normal tissue were more likely to express CD163, while epithelioid macrophages in regions where bacteria reside strongly expressed CD11c, CD68 and HAM56. Calprotectin-positive neutrophils were abundant in regions adjacent to caseum. iNOS, eNOS, Arg1 and Arg2 proteins were identified in macrophages and localized similarly in granulomas across species, with greater eNOS expression and ratio of iNOS:Arg1 expression in epithelioid macrophages, as compared to cells in the lymphocyte cuff. iNOS, Arg1 and Arg2 expression in neutrophils was also identified. The combination of phenotypic and functional markers support that macrophages with anti-inflammatory phenotypes localized to outer regions of granulomas while the inner regions were more likely to contain macrophages with pro-inflammatory, presumably bactericidal, phenotypes. Together these data support the concept that granulomas have organized microenvironments that balance anti-microbial anti-inflammatory responses to limit pathology in the lungs.